Analysis Winds Data from ASCAT and SAR Backscatter using Statistical and Modeling Methods during Tropical Cyclone Anggrek (2024) in Indian Ocean - Amabel Amedea Santoso Annisa; Wicaksono Ashari (BIO Web of Conferences)
Tropical cyclones are extreme weather phenomena characterized by strong winds that can cause damage to coastal areas, so accurate measurement of wind speed during tropical cyclones is very important. This study aims to measure the intensity of wind speed during the occurrence of Tropical Cyclone Anggrek in 2024 using microwave data from Synthetic Aperture Radar (SAR) and Advanced Scatterometer (ASCAT), both of which have different wind speeds in each measurement product. The methods used in this study include statistical analysis of wind speed data obtained from both sources, and data adjustment using the CMOD7D-v2 model to achieve consistency between SAR and ASCAT wind speed estimates. The results of the analysis show that this adjustment can reduce the SAR and ASCAT wind errors and show lower bias values. This research is expected to help the use of CMOD7D adjustment for wind speed analysis during tropical cyclones. CMOD7 GMF adjustment can help eliminate wind speed differences between SAR and ASCAT data, the analysis results show that the wind speed bias is reduced by 25.07% on January 27, while on January 29 it is reduced by 4.39%.